Antimicrobial evaluation of methyl 4-O-Acetyl-α-L-Rhamnopyranoside derivatives (Chittagong University Journal of Biological Sciences, 2013)
A number of 2,3-di-O-acyl derivatives (6-11) of methyl 4-O-acetyl-a-Lrhamnopyranoside (5) obtained by using various acylating agents were screened for in vitro antifungal activity against four plant pathogenic fungi, viz., Alternaria alternata, Curvularia lunata. Fusarium equiseti and Macrophomina phaseolina. These compounds were also screened for in vitro antibacterial activity against ten human pathogenic bacteria, viz., Bacillus subtilis, Bacillus cereus, Bacillus megaterium, Staphylococcus aureus, Escherichia coli, INABA ET (Vibrio), Pseudomonas species, Salmonella paratyphi, Shigella dysenteriae and Salmonella typhi. The study reveal that these 4-O-acetyl-?-L-rhamnopyranoside derivatives are more prone towards antifungal activities than that of antibacterial activities. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13404 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):33-43, 2008